Non-Governmental organizations in the mediation of violent intra-state conflict: the confrontation between theory and practice in the Mozambican peace process - Branco, Carlos (2014)
This essay discusses the role of NGOs in the mediation of violent intra-state conflicts. Based on the analysis of the Mozambican peace process, we tried to understand if informal actors and NGOs in particular would be best suited to mediate this type of conflict, as advocated by some. Against this current of thought, the author argues that official diplomacy still remains the most appropriate tool to lead the mediation of violent intra-state conflicts. In cases where multiple resources are used (multi-track), as was the case in Mozambique, formal actors and states, in particular, continued to play a decisive and unavoidable role because they had the resources that were not available to informal players. Informal diplomacy can complement formal diplomacy, but cannot replace it, and will always play a secondary and supporting role.